Tangerang Old Market MSMEs as Culinary Tourism Drivers: The Impact of Economic, Social and Culture - Raihan, Moh Aldi; Nurelisah, Siti Hazar (Lentera Ilmu Nusantara, 2025)
This study is to examine how MSMEs in Tangerang Old Market promote culinary tourism and its impact on the social, cultural, and economic aspects of the local economy. The urgency of this research lies in the growing importance of culinary tourism as a driver for regional development and the need to understand how MSMEs contribute beyond economic metrics. Surveys are used to collect data for quantitative research approaches, and multiple linear regression is used to analyze the results. Data were processed using SPSS software as the primary analysis tool to determine the significance and strength of the variables. The findings of the study show that the presence of MSMEs in an area is not significantly influenced by the variables of economic impact. Meanwhile, social and cultural impact variables have a great influence. The main things that support the sustainability of MSMEs are good service, good social interaction, and maintaining local culture. In addition to providing guidance to policymakers on how to develop initiatives that promote the sustainability of MSMEs, this research also highlights the importance of social and cultural roles in maximizing MSMEs' contribution to culinary tourism.